Cultural digital map prototype of tourist attractions in NirasSuphan written by SunthonPhu, poet of Thailand - Watcharee Phetwong (2018)
© Springer International Publishing AG 2016. NirasSuphan is poem written by SunthonPhu explaining the trip from ThepThida Temple, Bangkok to PahLuk, Danchang District in Suphanburi province. It was written in 2374 B.E. and recites the trip to find a leklai, a metal charm believed to melt when exposed to fire, which was believed to be a kind of elixir. The literature is significant to Suphanburi province since it describes how people lived in the past. The objective of this research was to design a digital map prototype of tourist attractions based on a sample of communities mentioned in the NirasSuphan and develop an accompanying web site to describe the communities along this route. One research study found that Thai tourists did not acknowledge having received guidance or having any existing awareness of cultural heritage. Developing a digital map for cultural tourist attractions could be a means of raising awareness of Thai cultural heritage.